2019 IEEE 58th Conference on Decision and Control (CDC) 2019
DOI: 10.1109/cdc40024.2019.9029561
|View full text |Cite
|
Sign up to set email alerts
|

Task-Space Bilateral Control of Teleoperators with Time-Varying Delay

Abstract: This paper investigates bilateral control of teleoperators with closed architecture and subjected to arbitrary bounded time-varying delay. A prominent challenge for bilateral control of such teleoperators lies in the closed architecture, especially in the context not involving interaction force/torque measurement. This yields the long-standing situation that most bilateral control rigorously developed in the literature is hard to be justified as applied to teleoperators with closed architecture. With a new cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…In our present study, we have observed a class of mathematical operations concerning differential functions, the application of which has also been witnessed in [34,35,37,33,38], and the most prominent example may be the one involving the introduction of stacked reference dynamics. This class of differential and integral operations is referred to as cascaded calculus (of differential functions along a differential equation), in contrast to the standard calculus that involves functions; in the context of control, we can refer to this class of operations as cascaded calculus along controlled dynamics around the input.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In our present study, we have observed a class of mathematical operations concerning differential functions, the application of which has also been witnessed in [34,35,37,33,38], and the most prominent example may be the one involving the introduction of stacked reference dynamics. This class of differential and integral operations is referred to as cascaded calculus (of differential functions along a differential equation), in contrast to the standard calculus that involves functions; in the context of control, we can refer to this class of operations as cascaded calculus along controlled dynamics around the input.…”
Section: Discussionmentioning
confidence: 70%
“…formulated; this approach has been demonstrated to be instrumental as handling time-varying delay (and switching topology) for networked Lagrangian systems or teleoperators [34,35,33]. Differing from the traditional order reduction paradigm [16,1], this differentialcascaded approach is an order invariance or increment one, and the resultant closed-loop dynamics are typically differential-cascaded.…”
Section: Introductionmentioning
confidence: 99%
“…By substituting M(θ) _ s from (31), dynamic adaptation law _ ϕ d from (25), and actuator adaptation law _ ϕ a from (26) into (33), we have…”
Section: Theorem 1 Consider the Closed-loop System Consisting Of Robmentioning
confidence: 99%
“…(2) e designed parameters φ and α are positive constants, which are also required to satisfy the relations α > 0, φ ≥ 0 and αφ ≤ 1. (3) e designed matrices Γ k and Γ d in (24) and (25) are required to be positive definite symmetric. e designed matrix Γ a is required to be positive definite diagonal.…”
Section: Theorem 1 Consider the Closed-loop System Consisting Of Robmentioning
confidence: 99%
See 1 more Smart Citation